联合国裁军年鉴 2018: 第二部分 - United Nations Office for Disarmament Affairs (United Nations, 2021)
The United Nations Disarmament Yearbook, volume 43 (Part II): 2018, with a foreword by the High Representative for Disarmament Affairs, summarizes developments and trends in 2018 on key issues of multilateral consideration at the international and regional levels; reviews the activity of the General Assembly, the Conference on Disarmament and the Disarmament Commission; and contains a handy timeline of highlights of multilateral disarmament in 2018.